The Effect of Dispositional Mindfulness on the Mental Health of Children Facing the Law in LPKA Class II Palu - Jusmawati Jusmawati; Dhevy Puswiartika; Munifah Munifah; Azam Arifyadi (FKIP - Universitas Riau, 2026)
Children who are in conflict with the law (ABH) are a group of adolescents who are vulnerable to experiencing mental health problems due to psychological pressure, limited freedom, and social stigma during the coaching period. One of the psychological factors that can support mental health is dispositional mindfulness. This study aims to examine the influence of dispositional mindfulness on the mental health of children who are facing the law at the Palu Class II Special Children's Development Institution (LPKA). The method used is a quantitative approach with an ex-post facto design. The research subjects consisted of 24 fostered children who were selected through total sampling techniques. The research data was obtained using the Five Facet Mindfulness Questionnaire (FFMQ) and Mental Health Continuum-Short Form (MHC-SF) instruments, then analyzed using descriptive statistics and simple linear regression. The results showed that the level of dispositional mindfulness was in the high category and mental health conditions were in the high category. However, the results of the regression analysis showed that dispositional mindfulness did not have a significant effect on mental health (p = 0.899; R² = 0.001). These findings suggest that the mental health of children who face the law is more influenced by other factors such as social support and a coaching environment.